PENDAMPINGAN PENGELOLAAN KEUANGAN SEDERHANA PADA UMKM JURAGAN PISANG KEMBUNG COKLAT KEJU DI KOTA SERANG UNTUK MENINGKATKAN KEBERLANJUTAN USAHA - Amyati, Amyati; Sari, Diah Permata; Sumarsih, Rani Sri (Yayasan Education and Social Center, 2026)
This community service activity aims to enhance business sustainability through simple financial management assistance for Juragan Pisang Kembung Coklat Keju MSME in Serang City. Many micro and small enterprises face sustainability challenges due to weak financial management practices, including the absence of systematic cash flow records and the mixing of personal and business finances. This program was conducted using a participatory and practical approach over one month in December 2025. The activities included initial observation, delivery of simple financial management materials, hands-on practice of daily cash flow recording and basic profit–loss calculation, as well as continuous mentoring and evaluation. The results show an improvement in participants’ understanding of financial management concepts and a positive change in managerial behavior, particularly in routine financial recording and cost control. Simple financial records enabled the MSME owner to better understand the actual financial condition of the business and to make more rational decisions. This community service demonstrates that simple and contextual financial management assistance can serve as an effective foundation for strengthening MSME resilience and long-term business sustainability.